2017
DOI: 10.5455/ijtrr.000000293
|View full text |Cite
|
Sign up to set email alerts
|

Shock Wave Therapy Versus Progressive Pressure Release on Myofascial Trigger Points

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In terms of the treated area, 22 studies were carried out on patients with cervical and shoulder complaints, three studies were conducted on the leg/foot region, 25,27,28 and two trials were conducted on the lumbar spine region. 22,30 On the duration of pain, eight studies reported no data on this variable, 19,20,23,28,32,33,38 five studies reported between zero days and 3 mos of pain duration, 18,24,29,33,34 and 14 studies reported that their sample had a duration of pain longer than 3 mos.…”
Section: Qualitative Summary Of the Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…In terms of the treated area, 22 studies were carried out on patients with cervical and shoulder complaints, three studies were conducted on the leg/foot region, 25,27,28 and two trials were conducted on the lumbar spine region. 22,30 On the duration of pain, eight studies reported no data on this variable, 19,20,23,28,32,33,38 five studies reported between zero days and 3 mos of pain duration, 18,24,29,33,34 and 14 studies reported that their sample had a duration of pain longer than 3 mos.…”
Section: Qualitative Summary Of the Included Studiesmentioning
confidence: 99%
“…The characteristics of the included studies are shown in Supplementary Appendix 2 (Supplemental Digital Content 3, http://links.lww.com/PHM/C68). Of the 27 RCTs included, 12 compared ESWT against a control ESWT, [17][18][19][20][21][22][23][24][25][26][27][28] and 18 compared ESWT, [17][18][19][20][21][22]26,[29][30][31][32][33][34][35][36][37][38][39] with other interventions. Most of the trials included two arms, except for six trials, which were three-armed studies.…”
Section: Qualitative Summary Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations